Nilai Karakter Pada Kearifan Lokal Nyadran Sebagai Sumber Pembelajaran IPS - Shafa Rizqi Nabilah; Sarmini Sarmini; Muhammad Turhan Yani (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2024)
Nyadran local wisdom is a routine because it is a form of community gratitude for the results of natural resources, especially in the fisheries sector. The aim of this research is to study and analyze the Nyadran tradition in Balongdowo Village, Sidoarjo. This research uses a qualitative method with a descriptive approach supported by participant observation, in-depth interviews with community leaders, and analysis of documentation related to the Nyadran tradition. The research results explain that the Nyadran tradition in Balongdowo Village is still carried out regularly every year as a way to honor ancestors and local traditions. However, the practice and meaning of this tradition have been influenced by modernization and social change. Despite this, the people of Balongdowo Village continue to try to maintain and harmonize Nyadran traditions with current social and cultural dynamics. The Nyadran tradition contains social, religious, and historical values ​​which are useful as teaching materials for social studies learning, especially in social and cultural change material. There needs to be efforts to preserve and adapt the Nyadran tradition so that it remains sustainable and meaningful for future generations.